Penerapan Hukum Pidana Terhadap Pelaku Penyelundupan Pengungsi Rohingya di Aceh - Nasution, Syahmuda Halim Dirga Mulia; Bintang, Hasdiana Juwita; Zarzani, T. Riza (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
People Smuggling is often considered a violation of human rights and akin to slavery. Many factors contribute to human trafficking in Indonesia, including a population that is less aware and concerned about the issue, corrupt practices that allow access to government law enforcement agencies, and a lack of law enforcement efforts to combat human trafficking. The increasing influx of Rohingya ethnic refugees in the Aceh region has also raised concerns among the community about the potential tarnishing of Islamic law that has long been upheld by the Acehnese people. The research problems to be discussed in this study are as follows: First, how does Indonesian law address human trafficking? Second, how are criminal penalties applied to perpetrators of human trafficking in Indonesia? This research is juridical-normative legal research. Secondary data were collected through a literature study related to the legal issues or problems posed in the research. Rohingya refugees arriving in Indonesia often become victims of human trafficking, and authorities have detained several perpetrators. The Directorate General of Immigration Regulation Number IMI-1489.UM.08.05 of 2010 further regulates the handling of illegal immigrants, who are subject to immigration actions in accordance with regulations. Illegal immigrants can be subjected to various administrative actions such as inclusion on prevention lists, deportation, or revocation of residence permits. Every legal violation has consequences stipulated by criminal law, with sanctions aimed at adding suffering. Article 10 of the Criminal Code divides types of criminal penalties into principal and additional penalties. This law also prescribes punishments for labor recruitment agents involved in human trafficking, as well as employers who exploit workers.